PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) DITINJAU DARI KEMAMPUAN BERPIKIR KREATIF PADA MATERI LUAS BANGUN DATAR SISWA KELAS V SEKOLAH DASAR - Hapsari, Wenti Tri; Sary, Ryky Mandar; Huda, Choirul (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to investigate the learning process using the Project-Based Learning (PjBL) model in relation to the creative thinking abilities of fifth-grade students on the topic of plane area. The research employed a Sequential Mixed Method with a Sequential Exploratory design. The subjects of this study were 24 fifth-grade students from SD N Panggung. Data collection instruments included an observation checklist, interview guidelines, test sheets, and a camera for documentation. The qualitative data were analyzed through four stages: data collection, data reduction, data display, and drawing conclusions. Quantitative data were analyzed using normality tests and t-tests. The results showed that during the